الاتجاه اللغوي لمعنى الاستواء وأثر الاعتزال فيه عند الزمخشري من خلال تفسيره الكشاف - Yahaya, Nasir; Samaila, Ali; Adam, Faiz Shuaib; Lul Abdul Ghani, Mubarak (Islamic Religious Education Departement, 2024)
Islamic thought has produced many intellectual and scientific schools, within which many personalities in different scientific fields have emerged. Al-Zamakhshari (d. 538H) is regarded as one of the most influential figures from the Mu’tazila school of thought in the history of Arab and Islamic culture. This study aims to reveal the direction and impact of Mu'tazila thought on the interpretation of verses related to Istiwa through Zamakhshari's book